THE IMPACT OF RESIDENTS ATTITUDE TOWARD SUSTAINABLE TOURISM DEVELOPMENT USING SUS-TAS: MEDIATING ROLE OF TOURISM INVOLVEMENT - Aprilia, Anisa; Aini, Edlyn Khurotul; Kumalasari, Kartika Putri; Fajar, Yusri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Currently, the concept of sustainable tourism development is critical, especially how local communities participate. This research aims to investigate the elements that influence the development of sustainable tourism in the biosphere reserve area of Alas Purwo National Park, Banyuwangi, namely environmental factors, social cost participation, and long-term planning mediated through tourism involvement. Using a survey method, the approach was empirically tested on a sample of 170 locals living close to the Alas Purwo National Park reserve. The questions are divided into two sections: the first includes socio-demographic and economic data on the respondents, and the second includes research tools made up of 25 questions utilizing a Likert scale with a maximum score of five. A questionnaire was administered to 170 respondents, who were subsequently evaluated using Structural Equation Modeling (SEM) with SmartPLS. All variables were found to have a substantial effect on sustainable tourism development, as mediated by the variable tourist involvement. The community has great potential to assist the growth of ecotourism that is sustainable. To manage tourism in a more sustainable manner, particularly in the biosphere region that needs to be conserved, the government, particularly local governments, local communities, and tourists are required.